Synthesis of (4-benzoyl-phenoxy)-acetic acid derivatives and their efficacy as antioxidant agents - Prashanth, T.; Ranganatha, V. Lakshmi; Naveen, P.; Gurupadaswamy, H.D.; Begum, A. Bushra; Al-Ghorbani, Mohammed; Khanum, Shaukath Ara (Free Radicals and Antioxidants)
Aim & background: To study the synthesis of a series of (4-benzoyl-phenoxy)-acetic acid derivatives (6aek) and to test their antioxidant activity. Methods: The newly synthesized compounds were characterized by IR, 1 H NMR and LCeMS analyses. All these compounds were screened for their in vitro antioxidant activity by employing 1,1-diphenyl-1- picrylhydrazyl (DPPH), nitric oxide (NO) and hydrogen peroxide (H2O2) radical scavenging assays. Results: Compounds 6h with chloro substituent in benzoyl ring and 6f with no substituent in benzoyl ring showed good radical scavenging activity in all the three methods compared to the standard drug ascorbic acid. Whereas compound 6k with methoxy substituent in benzoyl ring showed good antioxidant activity only in hydrogen peroxide method and remaining compounds showed moderate to mild radical scavenging activity. Conclusion: Compounds 6f, 6h and 6i showed excellent activity, almost equivalent to that of standard and the remaining compounds showed moderate to mild scavenging activity.
Keywords: Benzophenone; Antioxidant activity; Radical scavenging assays; Ascorbic acid